2008
DOI: 10.1111/j.1399-302x.2008.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting demonstrates that inducible nitric oxide synthase is not essential for resistance to oral candidiasis in mice, or for killing of Candida albicans by macrophages in vitro

Abstract: These data suggest that iNOS-derived NO is not required for resistance to oral candidiasis in vivo, and that bone marrow-derived macrophages may have iNOS-independent means of generating reactive nitrogen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…These results argue that NO production by activated macrophages during phagocytosis does not have a direct fungicidal effect on Coccidioides . Similar results were reported by Farah and coworkers [27], who observed no statistically significant difference in the ability of iNOS − / − - and WT murine strain-derived BMDM to kill C. albicans yeast in vitro . In contrast to our findings, however, they reported that macrophages from iNOS − / − mice phagocytosed a significantly greater percentage of yeast than BMDM isolated from wild type, control mice.…”
Section: Discussionsupporting
confidence: 91%
“…These results argue that NO production by activated macrophages during phagocytosis does not have a direct fungicidal effect on Coccidioides . Similar results were reported by Farah and coworkers [27], who observed no statistically significant difference in the ability of iNOS − / − - and WT murine strain-derived BMDM to kill C. albicans yeast in vitro . In contrast to our findings, however, they reported that macrophages from iNOS − / − mice phagocytosed a significantly greater percentage of yeast than BMDM isolated from wild type, control mice.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we did not observe any significant differences in the levels of selected proinflammatory cytokines or chemokines between the WT and iNOS −/− mice at 7 or 11 days postchallenge. Similar results have been reported by Farah and coworkers [16] who observed that WT and iNOS −/− mice infected with Candida albicans showed equivalent levels of expression of inflammatory cytokines measured by QRT-PCR. In contrast, Livonesi et al, [14] found that iNOS −/− mice infected with Paracoccidioides brasiliensis yeast cells showed higher levels of Th1 and Th2 cytokines than the WT strain, and proposed that elevated iNOS activity contributes significantly to both protection and regulation of the inflammatory response to this fungal pathogen.…”
Section: Discussionsupporting
confidence: 91%
“…For example, NO produced by macrophages has been reported to have both host tissue damaging and anti-inflammatory effects as a result of its modulation of host secretion and function of certain cytokines, chemokines and growth factors in response to a microbial insult [2]. Previous studies of Candida infections have concluded that macrophages obtained from WT and iNOS −/− mice showed no difference in their ability to kill the pathogen in vitro [16]. Regulation of iNOS activity occurs both at the transcriptional and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inducible nitric oxide synthase (iNOS or NOS2) is the major source of NO that is generated by phagocytes as an antimicrobial defence. Interestingly data from NOS2 knockout mice suggests that this enzyme is dispensible for clearance of oral candidiasis and for killing by macrophages (Farah et al, 2009). In addition nitrosative stress response genes were not found to be upregulated in C .…”
Section: Discussionmentioning
confidence: 99%